Auditory brain stem responses in infants with posthaemorrhagic ventricular dilatation. Issue 1 (January 1989) - Lary, S; De Vries, L S; Kaiser, A; Dubowitz, L M; Dubowitz, V
Abstract : Nineteen infants with posthaemorrhagic ventricular dilatation had auditory brain stem responses measured during the period of maximal ventricular dilatation. These showed various patterns ranging from normal, through various abnormalities, to complete absence of responses. When serial auditory brain stem responses were studied in parallel with the evolution of posthaemorrhagic ventricular dilatation it was seen that the abnormalities of auditory brain stem response usually resolved irrespective of the persistence or progression of ventricular dilatation. No correlation was found between cerebrospinal fluid pressure and prolonged interpeak intervals on the auditory brain stem response. In three patients with posthaemorrhagic ventricular dilatation improvement in the auditory brain stem response occurred when cerebrospinal fluid was withdrawn. Intermittent withdrawal of cerebrospinal fluid (by ventricular tap or lumbar puncture) in two of these infants was followed by improvement in the auditory brain stem response after a period of 24 hours (but not sooner). In one infant born at full term improvement in the auditory brain stem response was noted one week after shunting.